Histone Acetyltransferase SlGCN5 Regulates Shoot Meristem and Flower Development in Solanum lycopersicum - Hawar, Amangul; Xiong, Shiqi; Yang, Zhen; Sun, Bo (Frontiers in Plant Science, 2022)
The histone acetyltransferase GENERAL CONTROL NON-REPRESSED PROTEIN5 (GCN5) plays important roles in plant development via epigenetic regulation of its target genes. However, the role of GCN5 in tomato, especially in the regulation of tomato shoot meristem and flower development, has not been well understood. Here, we found that silencing of Solanum lycopersicum GCN5 (SlGCN5, Solyc10g045400.1.1) by virus-induced gene silencing (VIGS) and RNA interference (RNAi) resulted in loss of shoot apical dominance, reduced shoot apical meristem (SAM) size, dwarf and bushy plant phenotype. Besides, we occasionally observed extra carpelloid stamens and carpels fused with stamens at late stages of flower development. Through gene expression analysis, we noticed that SlGCN5 could enhance SlWUS transcript levels in both SAM and floral meristem (FM). Similar to the known function of GCN5 in Arabidopsis, we demonstrate that SIGCN5 may form a histone acetyltransferase unit with Solanum lycopersicum ALT ERATION/DEFICIENCY IN ACTIVATION2 a (SlADA2a) and SlADA2b proteins in tomato. Therefore, our results provide insights in the SlGCN5-mediated regulation of SAM maintenance and floral development in tomato.